Analysis Of Student Errors On Algebraic Form Material Based On Kastolan - Hasanah, Rizatul; Yuanita, Putri; Saragih, Sehatta; Roza, Yenita (Universitas Islam Ahmad Dahlan (UIAD), 2023)
Algebraic calculation operations are basic material that is the basis for studying other mathematical material, but there are still many students who still make mistakes in solving algebraic calculation operation questions. Therefore, it is necessary to analyze the errors made by students in working on algebraic calculation operations questions. This research aims to describe the errors made by students when completing algebraic operations according to Kastolan theory in solving algebraic arithmetic operation problems. This type of research is qualitative descriptive research. The data collection technique used was a test. The data analysis techniques used were: examining the results of students' answers by identifying and analyzing the types of errors made by students in answering questions related to the Kastolan error type; 1) Calculate the percentage of error for each type of error, 2) The results of the percentage level are classified based on the percentage of error, 3) The data that has been obtained is then calculated and will be carried out using descriptive analysis, 4) Make conclusions from the results of the analysis of students' errors in working on form operation questions algebra based on the Kastolan error type. Based on the research data and discussions obtained, 69% of conceptual errors were in the high category, 58% of procedural errors were in the sufficient category, and 59% of technical errors were in the sufficient category. It can be concluded that the mistakes that many students make when working on test questions are conceptual errors, namely errors in understanding the questions. Factors that cause students to make mistakes are not understanding the concept and not being able to apply the concept